2018
DOI: 10.1590/1414-431x20186982
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal tobacco smoke reduces thermogenesis capacity in brown adipose tissue in adult rats

Abstract: Maternal smoking is a risk factor for progeny obesity. We have previously shown, in a rat model of neonatal tobacco smoke exposure, a mild increase in food intake and a considerable increase in visceral adiposity in the adult offspring. Males also had secondary hyperthyroidism, while females had only higher T4. Since brown adipose tissue (BAT) hypofunction is related to obesity, here we tested the hypothesis that higher levels of thyroid hormones are not functional in BAT, suggesting a lower metabolic rate. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Whilst there was increased fat mass and unchanged fatty acid metabolic marker Cpt1α, plasma TG was not affected by maternal programming nor postnatal HFD consumption, which might be due to the mouse strain specific. It has previously been shown that with cigarette SE only during lactation, there were decreased proteins levels of Ucp1 and Cpt1 and reduced sympathetic nerve stimulation upon BAT in female adult rat ( 55 ). The same was observed with the administration of isolated nicotine through minipumps on the dams at the same period ( 56 ).…”
Section: Discussionmentioning
confidence: 97%
“…Whilst there was increased fat mass and unchanged fatty acid metabolic marker Cpt1α, plasma TG was not affected by maternal programming nor postnatal HFD consumption, which might be due to the mouse strain specific. It has previously been shown that with cigarette SE only during lactation, there were decreased proteins levels of Ucp1 and Cpt1 and reduced sympathetic nerve stimulation upon BAT in female adult rat ( 55 ). The same was observed with the administration of isolated nicotine through minipumps on the dams at the same period ( 56 ).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the extent of nicotine-or cigarette smoke-elicited effects on brown or "beige" adipocytes are still very limited. In this respect, recent research has shown that neonatal CS exposure evoked decreased thermogenic capacity of brown fat at an adult age [38]. Nicotine treatment of 3T3-L1 pre-adipocytes exhibited a complex effect depending on which stage of differentiation towards beige adipocytes occurred the exposure; at the early differentiation stage, the beige-like phenotype was impaired, whereas it was enhanced when nicotine was administered only at the later, "maintenance" stage or during the entire differentiation process [39].…”
Section: Discussionmentioning
confidence: 99%
“…The food restriction during pregnancy is the most common maternal stress ( Smart and Dobbing, 1971 ; Hales and Barker, 1992 ; Roseboom et al, 2001 ). However, obesity, diabetes ( Armitage et al, 2008 ; Shankar et al, 2008 ; Agarwal et al, 2018 ), stressful life events, air pollution ( Burris and Baccarelli, 2017 ; Almeida et al, 2019 ; Wang et al, 2020 ), nicotine/tobacco smoke ( Butler and Goldstein, 1973 ; Khorram et al, 2010 ; Santos-Silva et al, 2013 ; Younes-Rapozo et al, 2013 ; Lisboa et al, 2017 ; Peixoto et al, 2018 ), and the use of synthetic glucocorticoids ( Guo et al, 2020 ; Li et al, 2020 ; Arias et al, 2021 ) are important factors influencing the offspring health in later life, since they disrupt maternal and offspring physiology. Although stress induces different signaling pathways, the glucocorticoids are key mediators of stress response ( Molnar et al, 2003 ; Moisiadis and Matthews, 2014a ; Facchi et al, 2020 ) and beside their important role in the acute stress condition, glucocorticoids can also chronically affect the offspring brain neuronal connectivity, stability, and maturation, which can modulate hypothalamic energy controlling pathways ( Arck et al, 2001 ; Sandman et al, 2011 ; Christian et al, 2013 ; Solano et al, 2016 ; Osborne et al, 2018 ; Schepanski et al, 2018 ; Nazzari et al, 2020 ; Figure 1 ).…”
Section: Maternal Stress Exposure: Contribution Of Glucocorticoids An...mentioning
confidence: 99%